2005
DOI: 10.1007/s10038-005-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic correlates of genetic variation in the gene encoding 5α-reductase type 1

Abstract: Androgens determine male secondary sexual characteristics and influence a variety of metabolic pathways. Circulating levels of androgens are highly heritable; however, the genes involved are largely unknown. The 5a-reductase enzymes types 1 and 2 responsible for converting testosterone to the more potent androgen dihydrotestosterone are encoded by the SRD5A1 and SRD5A2 genes, respectively. We performed indirect genetic association studies of SRD5A1 and SRD5A2 and the dihydrotestosterone/testosterone ratio that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…12 In humans, Type I 5á-reductase is found primarily in the sebaceous glands of most regions of skin including scalp, and in liver, muscle, and brain (31,140), with low levels also present in prostate that may increase in prostate cancer (142). Type I 5á-reductase is responsible for approximately one-third of circulating DHT (58).…”
Section: Pharmacodynamics and Pharmacokinetics 5á-reductase Isozyme Smentioning
confidence: 99%
“…12 In humans, Type I 5á-reductase is found primarily in the sebaceous glands of most regions of skin including scalp, and in liver, muscle, and brain (31,140), with low levels also present in prostate that may increase in prostate cancer (142). Type I 5á-reductase is responsible for approximately one-third of circulating DHT (58).…”
Section: Pharmacodynamics and Pharmacokinetics 5á-reductase Isozyme Smentioning
confidence: 99%
“…13 Reports of associations between the A49T and V89L polymorphisms and plasma androgen levels, including testosterone and 3a-diolG, have been limited. [14][15][16][17] A single study has reported a null association between the V89L variant and balding patterns in European men.…”
mentioning
confidence: 99%
“…Indeed, the previously reported lack of association between diabetes and rs248793 25,26 allowed the use of a single healthy group of controls for both PAD subgroups.…”
Section: Single Nucleotide Polymorphism Rs248793 (G/c) Of the Srd5a1mentioning
confidence: 99%